Isolation of the compounds from antimicrobial active fraction from the stem barks of Entada spiralis Ridl - Mat So'ad, Siti Zaiton; Harun, Aiza; Mohd Hassan, Norazian; Che Mohd Ramli, Neni Kartini (2011)
Entada spiralis Ridl. which is locally known as Sintok or Beluru is a woody climber with a characteristic spiral stem. The stem bark is traditionally used as natural shampoo and body wash among Malays due to its high content of saponins and its medicinal properties. The methanol extract of the stem bark possess promising antimicrobial activity against some species of skin diseases caused microbes The extract was further fractionation with different solvent gradient and repeated test on dermatophytes were done. The most active fraction is chloroform: methanol(9:1(V/V)). From this fraction we managed to isolate five compounds. The structure elucidation of the compounds were based on spectroscopic data ( 1H and 13C NMR, HMQC, HMBC and DEPT135).